Exploring the role of safety culture dimensions in patient safety using a Bayesian Belief Network model - Simsekler, Mecit Can Emre; Qazi, Abroon; Ozonoff, Al (Safety science, 2025)
•Safety culture is multi-dimensional, significantly impacting patient safety outcomes.•A Bayesian Belief Network (BBN) model reveals key safety culture influences on patient safety.•The BBN model quantifies the strength of safety culture dimensions on patient outcomes.•The BBN approach offers a novel visualization of probabilistic relationships in safety culture.•This study guides resource allocation by prioritizing critical safety culture factors. There is a growing recognition of the impact of a multi-dimensional safety culture on patient safety practices within healthcare organizations. Despite this awareness, understanding the relationships among safety culture dimensions and their relative importance in dynamic and complex healthcare delivery remains unclear. To address this gap, we developed a Bayesian Belief Network (BBN) model to quantitatively assess the significance of various safety culture dimensions in influencing patient safety. Utilizing Hospital Survey on Patient Safety Culture (HSOPSC) SOPS Hospital Survey 2.0 data from U.S. teaching hospitals, this study provides insights into the strength of influence among interconnected variables, explores primary factors contributing to the patient safety, and offers guidance for decision-makers on optimal resource utilization by prioritizing safety culture dimensions based on their relative importance. Our findings identify three leading dimensions of safety culture for their significant association with patient safety ratings: ’communication openness,’ ’supervisor support for patient safety,’ and ’organizational learning – continuous support’. This analysis supports decision-making, providing insights into the relative priority of safety culture dimensions for optimal resource allocation. The BBN is a novel methodology, providing a visual representation of the probabilistic relationships and potential approaches for enhancing patient safety within healthcare settings.